Prevalence of Geriatric Syndromes Among Older Outpatients with Dementia - Luc Viet Tran; Thanh Xuan Nguyen; Thu Thi Hoai Nguyen; Huong Thi Thu Nguyen; Tam Ngoc Nguyen; Anh Lan Nguyen; Vasikaran Naganathan; Janani Thillainadesan; Huong Thi Thanh Nguyen; Anh Trung Nguyen; Huyen Thi Thanh Vu (Dementia and Geriatric Cognitive Disorders Extra, 2024)
Introduction The identification of geriatric syndromes in people with dementia is important. The aim of the study was to assess the prevalence of geriatric syndromes among dementia outpatients. Methods A cross-sectional study was conducted enrolling outpatients with dementia aged ≥ 60 years old. Dementia was diagnosed by neuropsychiatrists following DSM-5 criteria. The geriatric syndromes assessed included nutritional status (Mini Nutritional Assessment Scale-Short Form), polypharmacy, comorbidities, alcohol use, depression (Quality of Life in Alzheimer Disease), functional status (Barthel Index, Instrumental Activities of Daily Living); lower body strength (30 seconds stand chair test), and frailty (Timed Up and Go test ≥ 14 seconds) Results A total of 87 participants was recruited in the study (mean age: 76.8±1.2 years; female: 65.5%). The median number of geriatric syndromes per participant was 5 (IQR=2), all participants had two or more geriatric syndromes. The most common geriatric syndromes were loss of independence (96.6% impairment in > 1 IADL task score and 74.7% dependency in physical function at based on Barthel Index), reduced lower body strength (86.2%), malnutrition and risk of malnutrition (78.2%) and frailty (67.8%). Current and history of smoking, drinking alcohol, using memantine therapy, malnourished and risk of malnourished were significant associated with increasing severity of dementia Conclusion The presence and co-incidence of geriatric syndromes is common among outpatients with dementia. These findings have important clinical implications in term of the assessment and service delivery for older adults in Vietnam. We are exploring ways to enhance our services to provide comprehensive, multidisciplinary approaches to screening, recognition, and treatment of geriatric syndromes in older adults with dementia.